2022
DOI: 10.1108/jabs-01-2022-0023
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic capabilities as a strategic flexibility enabler: organizational responsiveness to COVID-19

Abstract: Purpose To cope with the existing pandemic situation and to be organizationally responsive, firms need to be strategically flexible, where they need to develop dynamic capabilities (DCs) by continuously reconfiguring their resource base. To address such challenges, firms heavily rely on information and communication technologies (ICT) because of advancement in disruptive technologies. This study aims to explore techniques used by higher education institutional (HEI) leaders to successfully address challenges p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 128 publications
(223 reference statements)
0
21
0
Order By: Relevance
“…Strong LC is especially valuable for SMEs to maximize limited resources. Muneeb et al (2022) suggested that knowledge begets creativity, stimulating firms to become more proactive, while Ali et al (2021) proved that learning skills enabled employees to use existing capabilities for innovation. This hypothesis is formally stated as:…”
Section: Learning Capabilitiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Strong LC is especially valuable for SMEs to maximize limited resources. Muneeb et al (2022) suggested that knowledge begets creativity, stimulating firms to become more proactive, while Ali et al (2021) proved that learning skills enabled employees to use existing capabilities for innovation. This hypothesis is formally stated as:…”
Section: Learning Capabilitiesmentioning
confidence: 99%
“…Research suggests that the relative smallness of SMEs allows them to leverage their "shorter distances" between individuals to improve communication, collaboration and coordination during turbulent times (Bodlaj and Cater, 2019). Evidence from many research studies supports the importance of CCs in FC (Nieves et al, 2016), but others have argued that these findings are incomplete because they were conducted during non-turbulent markets (Muneeb et al, 2022). During a crisis such as the recent pandemic, effective coordination of resources and activities is crucial as the market becomes more erratic and unpredictable.…”
Section: The Moderating Effect Of Market Turbulence On Dynamic Capabi...mentioning
confidence: 99%
See 3 more Smart Citations